PO266 Targeted treatment for cognitive impairments following traumatic brain injury with methylphenidate. (1st December 2017) - Jenkins, Peter; Simoni, Sara De; Bourke, Niall; Cole, James; Sharp, David
Abstract : Objectives: To investigate whether: 1) treatment with methylphenidate improves cognition following traumatic brain injury (TBI); 2) brain dopamine levels predict the magnitude of any improvement in symptoms. Background: Cognitive problems following TBI are common. The heterogeneous nature of TBI means that the basis of these cognitive deficits is likely to be multi-factorial. Previous studies show dopaminergic dysfunction following TBI. Drugs that increase dopamine in the brain, such as methylphenidate, are sometimes used to enhance cognition after TBI. The response to treatment, however, can be highly variable between patients. Therefore, what is needed is a way to target the use of these drugs to patients who are likely to respond. Methods: 40 moderate/severe TBI patients with persistent cognitive problems were randomised into a double-blind, placebo-controlled, cross-over design study. The primary outcome measure is whether improvement in the 'Choice Reaction Time' task with methylphenidate is predicted by specific binding ratio of the dopamine transporter in the caudate as measured by DaTscan. Results: The study is complete and unblinding is due at the end of January 2017. Conclusions: We will report the results of this large study, which is the first to relate imaging measures of the dopaminergic system to treatment response.